A critical reassessment of ambulance service airway management in prehospital care: Joint Royal Colleges Ambulance Liaison Committee Airway Working Group, June 2008. Issue 3 (19th March 2010) - Deakin, Charles D; Clarke, Tom; Nolan, Jerry; Zideman, David A; Gwinnutt, Carl; Moore, Fionna; Ward, Michael; Keeble, Carl; Blancke, Wim
Abstract : Paramedic tracheal intubation has been practised in the UK for more than 20 years and is currently a core skill for paramedics. Growing evidence suggests that tracheal intubation is not the optimal method of airway management by paramedics and may be detrimental to patient outcomes. There is also evidence that the current initial training of 25 intubations performed in-hospital is inadequate, and that the lack of ongoing intubation practice may compound this further. Supraglottic airway devices (eg, laryngeal mask airway), which were not available when extended training and paramedic intubation was first introduced, are now in use in many ambulance services and are a suitable alternative prehospital airway device for paramedics.